Handel opera presentation, past and present : a thesis presented in partial fulfilment of the requirements for the degree of Master of Music at Massey University, Wellington, New Zealand - Tweedie, Shannon (Massey University, 2004)
What differences, if any, exist between the performance of Handel opera during his lifetime, and contemporary performances? To what extent do these differences reflect the need to adapt Handel's operas when performed out of their original context, and how does knowledge of original performance practices enhance the singer's ability to interpret and present characters in performance? This study investigates the ideas outlined above, exploring the social and cultural environment of opera seria, its conventions, and the way in which Handel's operas were presented during his lifetime, later providing a comparison with contemporary productions. It aims to enhance understanding of the production and musical aspects of staging a Handel opera, and to illustrate how this knowledge can assist in performance.
Keywords: Handel George Frideric 1685-1759; Dramatic production; Singing; Interpretation (Phrasing, dynamics, etc); Acting in opera; Opera; Production and direction